Melatonin Increases the Sensitivity of Osteosarcoma Cells to Chemotherapy Drug Cisplatin - Hosseini, Foroogh; Shanehbandi, Dariush; Soleimanpour, Jafar; Yousefi, Bahman; Alemi, Forough (Drug Research, 2022)
Chemotherapy, which is one of the common treatments for osteosarcoma (OS), has many side effects and in some cases has low effectiveness due to chemoresistance, hence it is vital to study new therapies for OS. In this regard, we combined melatonin with cisplatin and evaluate their effect on MG63 OS cells. Since melatonin has anti-cancer properties, we hypothesized that its combination with cisplatin could increase the effectiveness of cisplatin. Firstly, MTT assay was used to evaluate the cell viability and cytotoxicity of cisplatin on MG63 cells and the results showed that melatonin in combination with cisplatin increases the sensitivity of MG63 cells to cisplatin. In addition, qRT-PCR results showed that the expressions of miR-181 and P53, CYLD, CBX7 and BCL2 genes change in MG63 cells after treatment with the combination of cisplatin and melatonin, so that the expression of P53, CYLD and CBX7 increased and the expression of BCL2 and miR-181b decreases significantly. Furthermore, analysis of Annexin V/FITC assay data revealed that the rate of apoptosis in MG63 OS cell line remarkably promoted after treated with cisplatin and melatonin combination. As a result, our findings show that melatonin in combination with cisplatin increases the effectiveness of cisplatin in osteosarcoma cells and this study provides a new therapeutic approach for OS.
Keywords: Bone cancer; cisplatin; combination therapy; P53; BCL2; non-coding RNA